Multivariate Entropy Analysis of Oxidative Stress Biomarkers Following Mobile Phone Exposure of Human Volunteers: A Pilot Study - Thomas, Yolene (Journal of Scientific Exploration, 2015)
A multidisciplinary project was conducted to study the possible biological impact of mobile phones emissions. As part of that project, we conducted a pilot study on 24 human volunteers with the treatment being GSM mobile phone exposure. The volunteers were randomized, and the study was a double-blind, crossover design. Two categories of oxidative stress biomarkers were followed and measured in blood and exhaled air: those assessing oxidative attacks of cell membrane lipids (malondialdehyde, exhaled alkanes, aldehydes, and isoprene) and those accounting for the organism's antioxidant defense systems (superoxyde dismutase, glutathion peroxydase, and exhaled halogenated alkanes). The overall entropy of the system with and without GSM exposure was then calculated for each volunteer, using a statistical approach based on the global entropic difference of raw data. A significant modulation of organization of the biomarkers after a single 30 minutes mobile phone exposure was found, as evidenced by a decreased entropy of the dataset associated to the emitting mobile phone condition. While these results illustrate neither deleterious effects nor innocuity of mobile phone use, they nonetheless constitute evidence of actual interactions of these wavelengths with complex biological systems. These results will need to be confirmed in larger, future studies.